Using public service advertising in teaching french as a foreign language in language departments - Andrianova, Natalia S. (2018)
One of the most important components of professional competence of a modern competitive specialist is a high level of foreign language communicative competence, which leads to the search for the most optimal ways of teaching foreign languages. The article deals with the linguistic and didactic potential of social advertising texts as an effective means of formation of intercultural communicative competence of students in teaching French as a foreign language. The importance and expediency of the use of social advertising in the classroom for the practice of speech and linguistic studies in the language University is being proved. Being an authentic resource, it contributes to the immersion of students in the socio-cultural reality of the country of the studied language and can act as an auxiliary tool in mastering the skills of listening, speaking and writing and the formation of intercultural communication. In the course of the study it was found that social advertising materials are not only one of the effective means of formation of foreign language communicative competence, information, analytical and creative skills of students, but also contribute to the formation of value orientations and behavioral models of modern students in accordance with specific social norms and ideals through polycode advertising text. Thus, it can be stated that social advertising is a means of moral and cultural enrichment of the individual.